T helper cell responses in adult diarrheal patients following natural infection with enterotoxigenic Escherichia coli are primarily of the Th17 type - Akhtar, Marjahan; Basher, Salima Raiyan; Nizam, Nuder Nower; Hossain, Lazina; Bhuiyan, Taufiqur Rahman; Qadri, Firdausi; Lundgren, Anna (Frontiers in Immunology, 2023)
Infection with enterotoxigenic Escherichia coli (ETEC) gives rise to IgA antibodies against both the heat labile toxin (LT) and colonization factors (CFs), which are considered to synergistically protect against ETEC diarrhea. Since the development of ETEC-specific long lived plasma cells and memory B cells is likely to be dependent on T helper (Th) cells, we investigated if natural ETEC diarrhea elicits ETEC-specific Th cells and their relation to IgA responses. Th cell subsets were analyzed in adult Bangladeshi patients hospitalized due to ETEC diarrhea by flow cytometric analysis of peripheral blood mononuclear cells (PBMCs) isolated from blood collected on day 2, 7, 30 and 90 after hospitalization as well as in healthy controls. The LT-and CF-specific Th responses were determined by analysis of IL-17A and IFN-γ in antigen stimulated PBMC cultures using ELISA. ETEC-specific IgA secreted by circulating antibody secreting cells (plasmablasts) were analyzed by using the antibodies in lymphocyte supernatants (ALS) ELISAbased method and plasma IgA was also measured by ELISA. ETEC patients mounted significant ALS and plasma IgA responses against LTB and CFs on day 7 after hospitalization. ETEC patients had significantly elevated proportions of memory Th cells with a Th17 phenotype (CCR6+CXCR3-) in blood compared to controls, while frequencies of Th1 (CCR6-CXCR3+) or Th2 (CCR6-CXCR3-) cells were not increased. Antigen stimulation of PBMCs revealed IL-17A responses to LT, most clearly observed after stimulation with double mutant heat labile toxin (dmLT), but also with LTB, and to CS6 in samples from patients infected with LTB+ or CS6+ ETEC bacteria. Some individuals also mounted IFN-γ responses to dmLT and LTB. Levels of LTB-specific IgA antibodies in ALS, but not plasma samples correlated with both IL-17A (r=0.5, p=0.02) and p=0.01) responses to dmLT. Our results show that ETEC diarrhea induces T cell responses, which are predominantly of the Th17 type. The correlations between IL-17A and IFN-γ and intestine-derived plasmablast responses support that Th responses may contribute to the development of protective IgA responses against ETEC infection. These observations provide important insights into T cell responses that need to be considered in the evaluation of advanced ETEC vaccine candidates.